Integrasi Augemented Reality dan Fun Sport Games Berbasis Aplikasi Interaktif Untuk Meningkatkan Aktivitas Fisik Anak TK di Kota Cirebon dengan Ruang Terbatas - Mia Rosalina; Zuki Kurniawan; Munaji Munaji; Nur Rahmadilla; Solihin Andhika (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This research focuses on promoting physical engagement among young learners in early childhood education environments by integrating Augmented Reality (AR) with interactive sport-based games at IGRA Pekalipan Kindergarten, Cirebon City. A developmental–implementation framework was employed, emphasizing the creation and utilization of an AR-driven application designed to support children’s movement activities within spatially constrained classrooms. The outcomes revealed a 25% improvement in both duration and intensity of physical involvement during the onemonth intervention. In addition, AR-integrated games significantly enhanced children’s participation, enthusiasm, and motor skill growth through engaging and playful learning interactions. Overall, the study demonstrates that AR innovation offers a creative and feasible strategy for fostering physical activity among early learners, particularly in environments with limited physical space.